Bernhard Brehmer & Jeanine Treffers-Daller (Eds): Lost in Transmission : The Role of Attrition and Input in Heritage Language Development - Sergei, Gnitiev (Universitas Muhammadiyah Muara Bungo, 2020)
This book review of key contribution to the description and explanation of variability in the outcomes of heritage language acquisition, taking into account a wide range of factors which impact on language acquisition. It summarize the role of attrition and input in heritage language development from Bernhard Brehmer & Jeanine Treffers-Daller Amsterdam, Philadelphia: John Benjamins Publishing Company, 2020. vii, 276 pp.